2021
DOI: 10.7759/cureus.14089
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholestasis of Pregnancy: Role of Baby’s Sex on Itch Severity and Bile Acid Levels

Abstract: Background Intrahepatic cholestasis of pregnancy (ICP) is the most common liver disorder of pregnancy. It occurs when bile flow from the liver is obstructed, causing bile acid to accumulate. ICP usually presents with itching that lasts for the remainder of pregnancy. Untreated ICP has been shown to increase the incidence of adverse outcomes for the baby, including respiratory distress, meconium aspiration, neonatal intensive care unit hospitalization, and stillbirth. The probability of these events increases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…There are conflicting reports about the association between maternal serum total bile acid levels and itching symptom in pregnant women with intrahepatic cholestasis of pregnancy. Bartolone, S. et al found a significant positive association between maternal serum total bile acid levels and itching symptom [8,37]; others have reported no relationship [38,39]. In our cohort, there was a significant positive correlation between itching symptom and serum total bile acid levels in pregnant women.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…There are conflicting reports about the association between maternal serum total bile acid levels and itching symptom in pregnant women with intrahepatic cholestasis of pregnancy. Bartolone, S. et al found a significant positive association between maternal serum total bile acid levels and itching symptom [8,37]; others have reported no relationship [38,39]. In our cohort, there was a significant positive correlation between itching symptom and serum total bile acid levels in pregnant women.…”
Section: Discussionsupporting
confidence: 42%
“…The incidence of intrahepatic cholestasis of pregnancy is reported to be between 0.2% and 2% but varies widely with ethnicity and geographic location. It is most common in South America and northern Europe [8][9][10]. There is a higher incidence of intrahepatic cholestasis of pregnancy in women with a multiple pregnancy (up to 22% in one study) [11,12].…”
Section: Introductionmentioning
confidence: 96%
“…In a study evaluating the role of fetal sex in 2289 documented ICP pregnancies, the number of male fetuses was higher than that of female fetuses despite being statistically insignificant, which correlates with our findings. [38] In our study, male sex was found to be a significant risk factor (56.5% vs 22.2%, P = .005).…”
Section: Discussionmentioning
confidence: 46%